Characterization of the EP receptor subtype that mediates the inhibitory effects of prostaglandin E2 on IgE‐dependent secretion from human lung mast cells. Issue 7 (21st June 2013) - Kay, L. J.; Gilbert, M.; Pullen, N.; Skerratt, S.; Farrington, J.; Seward, E. P.; Peachell, P. T.
Summary Background Prostaglandin E2 (PGE2) has been shown to inhibit IgE‐dependent histamine release from human lung mast cells. This effect of PGE2 is believed to be mediated by EP2 receptors. However, definitive evidence that this is the case has been lacking in the absence of EP2‐selective antagonists. Moreover, recent evidence has suggested that PGE2 activates EP4 receptors to inhibit respiratory cell function. Objective The aim of this study was to determine the receptor by which PGE2 inhibits human lung mast cell responses by using recently developed potent and selective EP2 and EP4 receptor antagonists alongside other established EP receptor ligands. Methods The effects of non‐selective (PGE2, misoprostol), EP2‐selective (ONO‐AE1‐259, AH13205, butaprost‐free acid) and EP4‐selective (L‐902, 688, TCS251) agonists on IgE‐dependent histamine release and cyclic‐AMP generation in mast cells were determined. The effects of EP2‐selective (PF‐04418948, PF‐04852946) and EP4‐selective (CJ‐042794, L‐161, 982) antagonists on PGE2 responses of mast cells were studied. The expression of EP receptor subtypes was determined by RT‐PCR. Results Prostaglandin E2, EP2 agonists and EP4 agonists inhibited IgE‐dependent histamine release from mast cells. PGE2 and EP2 agonists, but not EP4 agonists, increased cyclic‐AMP levels in mast cells. EP4‐selective antagonists did not affect the PGE2 inhibition of histamine release, whereas EP2‐selective antagonists caused rightward shifts in the PGE2 concentration–response curves. RT‐PCR studies indicated that mast cells expressed EP2 and EP4 receptors. Conclusions and Clinical Relevance Although human lung mast cells may express both EP2 and EP4 receptors, the principal mechanism by which PGE2 inhibits mediator release in mast cells is by activating EP2 receptors.